Ravishing Vancouver Circa 1948: Life Writing and the Immersive Translation of Noir Aesthetics (Imaginations: Journal of Cross-Cultural Image Studies, 2021)
This article takes its cues from autobiography scholar Marlene Kadar’s expansive, archivally focused feminist approach to life writing in its examination of two exemplars of visual culture: Ivan Sayers and Claus Jahnke’s From Rationing to Ravishing: The Transformation of Women’s Fashion in the 1940s & 1950s exhibition and Stan Douglas’s innovatively staged Helen Lawrence and its sister project, the interactive app and installation, Circa 1948. It illuminates both works biographically, exploring their creators’ relation to Vancouver to better understand the resurgence of noir in Vancouver circa 2014 as a form of translation intended to make historical lessons about crime and corruption visible for those willing to see them.
Keywords: noir; Vancouver; fashion exhibitions; Stan Douglas; life writing